1979
DOI: 10.1042/cs057321s
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Whole-Body and Cellular (Erythrocytes) Turnover of 22Na+ in Normotensive Relatives of Probands with Established Essential Hypertension

Abstract: 1. Whole-body elimination rate of 22Na+ was decreased in normotensive or borderline first-degree relatives of hypertensive probands. 2. Whole-body potassium, exchangeable sodium and urine excretion of sodium, potassium and creatinine were similar in relatives and controls. 3. Erythrocyte net influx of 22Na+ was significantly increased in normotensive relatives. 4. Abnormal whole-body and cellular handling of sodium (22Na+) demonstrated in relatives indicates that this abnormality may have an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Alterations in red cell Na-K cotransport, sodium permeability, total sodium efflux, and sodium influx in hypertensives have all been described."" 14 Additional investigators have worked with leucocytes. 29 " 31 Contradictory findings have been reported and the relationships among various assays are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in red cell Na-K cotransport, sodium permeability, total sodium efflux, and sodium influx in hypertensives have all been described."" 14 Additional investigators have worked with leucocytes. 29 " 31 Contradictory findings have been reported and the relationships among various assays are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1 " 14 Previous case control studies have demonstrated a relationship between sodium-lithium (Na-Li) countertransport and hypertension. '-7 -15~17 This report described the results of a populationbased cross-sectional survey in employed white men relating levels of countertransport to the presence of hypertension.…”
mentioning
confidence: 99%
“…(29) and Henningsen et al (15) show an increased erythrocyte sodium level in hypertensive patients and their normotensive relatives. Potassium levels are presumably altered concomitantly, since the intracellular contents of sodium and potassium are closely related by the active alkali cation transport system and the diffusion along the ion gradient (5).…”
mentioning
confidence: 95%
“…Lately, research on the cellular effects of the sodium ion (5)(6)(7)(8)(9) and the influence of salt intake on the activity and effects of the sympathetic nervous system (10,11) has again increased interest in the role of sodium in the regulation of the blood pressure and in the development of essential hypertension.…”
Section: Introductionmentioning
confidence: 99%